What determines adult cognitive skills? Influences of pre-school, school, and post-school experiences in Guatemala - Jere R. Behrman; John Hoddinott; John A. Maluccio; Erica Soler-Hampejsek; Emily L. Behrman; Reynaldo Martorell; Manuel Ramírez-Zea; Aryeh D. Stein (Latin American Economic Review, 2014)
Most empirical investigations of the effects of cognitive skills assume that they are produced by schooling. Drawing on longitudinal data to estimate production functions for adult verbal and nonverbal cognitive skills, we find that: (1) School attainment has a significant and substantial effect on adult verbal cognitive skills but not on adult nonverbal cognitive skills; and (2) Pre-school and post-school experiences also have substantial positive significant effects on adult cognitive skills. Pre-school experiences captured by height for age at 6 years substantially and significantly increase adult nonverbal cognitive skills, even after controlling for school attainment. Post-school tenure in skilled jobs has significant positive effects on both types of cognitive skills. The findings (1) reinforce the importance of early life investments; (2) support the importance of childhood nutrition ("lynn effect" and work complexity in explaining increases in nonverbal cognitive skills; (3) call into question interpretations of studies reporting productivity impacts of cognitive skills that do not control for endogeneity; and (4) point to limitations in using adult school attainment alone to represent human capital.
Keywords: I2; O1; 330; Cognitive skills; Schooling; Guatemala; Nutrition